Kajian Permasalahan Pembinaan Sistem Saliran Yang Menjadi Punca Kepada Masalah Banjir Di Kawasan Perumahan - Che Hassan, Munirah; Shareh Musa, Sharifah Meryam; Zainal, Rozlin; Kasim, Narimah (Research in Management of Technology and Business, 2020)
Flooding is a natural disaster that occurs every year which causes property damage, environmental damage and loss of life. Flooding also caused almost all houses and residential areas to be flooded. Flood events can be caused by issues such as drainage systems being blocked by waste disposal, failure to maintain the maintenance of drainage systems and so on. In this regard, the study was conducted to identify the types of drainage systems that were built, to investigate problems in the drainage system that caused flooding and to suggest ways of improving the drainage system in residential areas. The areas involved in this study were in several residential parks in the Tanah Merah, Kota Bharu and Pasir Mas districts. For data collection, the researcher used the interview method of 11 respondents comprising Department of Irrigation and Drainage (JPS), Local Authorities (PBTs) and residents of the area and observation method to study the specification of existing drainage in the area. As a result of the interviews conducted, it was found that drainage systems in residential areas consist of U, V, Half and cascading drainage systems. The drainage system has problems with clogged drainage system problems, poor maintenance, and poor quality of life and so on. Therefore, improvements should be made to avoid any unwanted problems. Some methods can be done such as upgrading the drainage system, deepening the river project and so on. It is hoped that the eleven respondents comprising Department of Irrigation and Drainage (JPS), Local Authorities (PBTs) developers and others will directly or indirectly need to take appropriate steps to reduce the problem in the construction of drainage systems that cause flooding in residential areas.